1998
DOI: 10.1093/jnci/90.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Immune Responses After Surgical Treatment for Regional Breast Cancer

Abstract: The data show that the physiologic effects of stress inhibit cellular immune responses that are relevant to cancer prognosis, including NK cell toxicity and T-cell responses. Additional, longitudinal studies are needed to determine the duration of these effects, their health consequences, and their biologic and/or behavioral mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
230
0
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 338 publications
(244 citation statements)
references
References 42 publications
(50 reference statements)
4
230
0
4
Order By: Relevance
“…The data suggest that early intervention could not only enhance short-term QoL but would likely decrease the negative impact of stress on long-term QoL for these patients. Furthermore, our previous work has found that traumatic stress symptoms (IES scores) measured at diagnosis/ surgery are also associated with a broad band of immune effects, including decreased natural killer cell lysis, natural killer responsiveness to biologic response modifiers, and T-cell blastogenesis (Andersen et al, 1998). With stress at diagnosis/surgery having such sweeping effects, interventions aimed at reducing stress (i.e., relaxation training, stress management, coping skills) appear especially important.…”
Section: Discussionmentioning
confidence: 99%
“…The data suggest that early intervention could not only enhance short-term QoL but would likely decrease the negative impact of stress on long-term QoL for these patients. Furthermore, our previous work has found that traumatic stress symptoms (IES scores) measured at diagnosis/ surgery are also associated with a broad band of immune effects, including decreased natural killer cell lysis, natural killer responsiveness to biologic response modifiers, and T-cell blastogenesis (Andersen et al, 1998). With stress at diagnosis/surgery having such sweeping effects, interventions aimed at reducing stress (i.e., relaxation training, stress management, coping skills) appear especially important.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that cancer-related stress correlated with impaired immunity in patients with invasive breast cancer [15]. This study of 116 patients after surgical resection of Stage II or Stage III breast cancer demonstrated decreased NK cell toxicity and T cell blastogenesis in patients exhibiting high levels of cancer-related psychological stress [15].…”
Section: Introductionmentioning
confidence: 87%
“…It has been extensively validated in studies of patients with diverse serious illnesses, including cancer [8,[13][14]. Significant reductions in cancer-associated psychological distress can be achieved with psychosocial interventions aimed at decreasing stress levels, strengthening social support networks, and improving coping and life management skills [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fear and anxiety coupled with cancer-related intrusive thoughts, age, socio demographic characteristics and financial concerns along with a tendency towards negativity (neuroticism) may conspire to heighten a women's risk for psychologic distress which in turn can worsen the treatment related symptoms such as nausea and vomiting, pain and psychologic distress [2,3].This can lead to helplessness/hopelessness, sleep disturbances, poor antitumor immune response, decrease in overall and disease free survival with early relapse/recurrence and heightened distress [4].…”
mentioning
confidence: 99%